Honduras : Public Expenditure Management for Poverty Reduction and Fiscal Sustainability - World Bank (Washington, DC, 2013)
As a highly indebted poor country, Honduras faces a dual challenge of reducing poverty while ensuring medium-term sustainability of its public spending to avoid recurrence of over indebtedness. This Public Expenditure Review (PER) is intended to contribute to the government's overall poverty reduction efforts through efficient use of public resources and fiscally sustainable improvement in public services. It provides an assessment of Honduras' institutional capacity for good expenditure management and identifies key policy priorities in selected sector (health, education, and infrastructure). A good institutional arrangement of effective public expenditure management requires achieving the three inter-related objectives of aggregate fiscal discipline, allocation of resources to strategic priorities, and operational efficiency. One of the problems in Honduras' public expenditure management that can be tackled immediately is the need for improvement in the budget classification system for better fiscal transparency. Besides, a medium-term expenditure framework (MTEF) is useful to guide budgetary decision-making that balances medium-term fiscal affordability/sustainability and strategic priorities of policies and expenditure programs. This report presents an illustration that emphasizes developing a MTEF for personnel expenditures, whose control is critical for fiscal sustainability and the government's ability to fund other critical spending item for poverty reduction.